Improving Children's Fine Motor Skills Through Natural Material Stringing Activities in Group A of Berlian Nupabomba State Kindergarten - Henny Priwati; Andi Agusniatih; Ika Juhriati (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
Early childhood is known as a golden period of child development that requires appropriate stimulation so that all aspects of development, especially fine motor skills, can develop optimally. In reality, the development of fine motor skills in children is not optimal due to teachers' limitations in the use of media and innovative learning methods. The purpose of this study was to develop children's fine motor skills through stringing activities that utilize natural materials, namely banana leaves. This study applied the Classroom Action Research (CAR) method with two cycles, which included the planning, implementation, observation, and reflection stages. As research subjects, 20 children from group A were selected, consisting of 8 boys and 12 girls. Data collection was carried out through observation, interviews, and documentation, then analyzed qualitatively through the stages of reduction, presentation, and drawing conclusions. The results of the study showed a significant increase in children's fine motor skills, especially in aspects of speed, flexibility, and finger strength. Stringing activities with banana leaves were proven to be able to provide a fun and meaningful learning experience, as well as train children's focus and perseverance. Based on these results, it can be concluded that the use of natural materials in creative activities is effective as a learning strategy in early childhood education. The contribution of this research lies in strengthening empirical evidence regarding the effectiveness of nature-based media as an innovative alternative that is environmentally friendly while also supporting the development of fine motor skills in early childhood.